A study on the awareness and preference of digital reference services of the Quezon City Public Library users - Espinosa, Zyra J. (2012)
Digital Reference Service (DRS) has been the new face of reference service; and because of its novelty many libraries in the Philippines are still discovering this new service. Thus, this study focuses on the current state of the DRS of the Quezon City Public Library (QCPL).